Prognostic factors for COVID-19 patients - Önal, Uğur; Aydın Güçlü, Özge; Akalın, Halis; Aylin Acet Öztürk, Nilüfer; Semet, Cihan; Demirdöğen, Ezgi; Görek Dilektaşlı, Aslı; Sağlık, İmran; Kazak, Esra; Özkaya, Güven; Coşkun, Funda; Ediger, Dane; et al. (The Journal of Infection in Developing Countries, 2022)
Introduction: Determining prognostic factors in patients with coronavirus disease (COVID-19) can have great impact on treatment planning and follow-up strategies. Herein, we aimed to evaluate prognostic factors and clinical scores for confirmed COVID-19 patients in a tertiary-care hospital in the Bursa region of Turkey. Methodology: Patients who had been diagnosed with COVID-19 microbiologically and/or radiologically between March and October 2020 in a tertiary-care university hospital were enrolled retrospectively. Adult patients (≥ 18 years) with a clinical spectrum of moderate, severe, or critical illness were included. The dependent variable was 30-day mortality and logistic regression analysis was used to evaluate any variables with a significant p value (< 0.05) in univariate analysis. Results: A total of 257 patients were included in the study. The mortality rate (30-day) was 14.4%. In logistic regression analysis, higher scores on sequential organ failure assessment (SOFA) (p < 0.001, odds ratio (OR) = 1.86, 95% CI = 1.42-2.45) and CURB-65 pneumonia severity criteria (p = 0.001, OR = 2.60, 95% CI = 1.47-4.57) were found to be significant in predicting mortality at admission. In deceased patients, there were also significant differences between the baseline, day-3, day-7, and day-14 results of D-dimer (p = 0.01), ferritin (p = 0.042), leukocyte (p = 0.019), and neutrophil (p = 0.007) counts. Conclusions: In our study of COVID-19 patients, we found that high SOFA and CURB-65 scores on admission were associated with increased mortality. In addition, D-dimer, ferritin, leukocyte and neutrophil counts significantly increased after admission in patients who died.